2020
DOI: 10.3390/cells9092070
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic High-Sensitivity Quantitation of Procollagen-I by Endogenous CRISPR-Cas9 NanoLuciferase Tagging

Abstract: The ability to quantitate a protein of interest temporally and spatially at subcellular resolution in living cells would generate new opportunities for research and drug discovery, but remains a major technical challenge. Here, we describe dynamic, high-sensitivity protein quantitation technique using NanoLuciferase (NLuc) tagging, which is effective across microscopy and multiwell platforms. Using collagen as a test protein, the CRISPR-Cas9-mediated introduction of nluc (encoding NLuc) into the Col1a2 locus e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 40 publications
(42 reference statements)
1
17
2
1
Order By: Relevance
“…Using this system, a GFP signal will only be present when VPS33b interacts with collagen-I. We, and others, have previously demonstrated that insertion of tags at the N-terminal of pro α 2(I) or pro α 1(I) chain does not interfere with collagen-I folding or secretion 29, 30 . To determine which terminus of the VPS33b protein GFP1-10 should be added, we inserted BFP on either the N-terminal (VPSnBFP) and C-terminal (VPScBFP) ends of VPS33b and imaged the cells.…”
Section: Resultsmentioning
confidence: 97%
“…Using this system, a GFP signal will only be present when VPS33b interacts with collagen-I. We, and others, have previously demonstrated that insertion of tags at the N-terminal of pro α 2(I) or pro α 1(I) chain does not interfere with collagen-I folding or secretion 29, 30 . To determine which terminus of the VPS33b protein GFP1-10 should be added, we inserted BFP on either the N-terminal (VPSnBFP) and C-terminal (VPScBFP) ends of VPS33b and imaged the cells.…”
Section: Resultsmentioning
confidence: 97%
“…To monitor the replication of SARS-CoV-2 we generated DNA sequences that encode the SARS-CoV-2 variant Wuhan-Hu-1 (NC_045512.2, wild-type) and a modified traceable virus where Orf7a is replaced with the sequence encoding NanoLuciferase (SARS-Cov-2-ΔOrf7a-NLuc, Figure 1A ). NanoLuciferase (NLuc) is an enzyme that produces light when supplied with its substrate (coelenterazine) and is readily detectable even at low quantities 2 . Orf7a has been removed in SARS-CoV and SARS-CoV-2 and yielded infectious viral clones 4–6 , it is not highly conserved in beta-coronaviruses, and several disrupting mutations of Orf7a of the non-structural protein are known 7 .…”
Section: Resultsmentioning
confidence: 99%
“…1A). NanoLuciferase (NLuc) is an enzyme that produces light when supplied with its substrate (coelenterazine) and is readily detectable even at low quantities (Calverley et al, 2020). Orf7a has previously been removed in SARS-CoV and SARS-CoV-2 and yielded infectious and replicative virus particles (Thi Nhu Thao et al, 2020;Xie et al, 2020a;Xie et al, 2020b).…”
Section: Generation Of a Traceable Sars-cov-2 Virusmentioning
confidence: 99%
See 2 more Smart Citations